Genetic relationship between multiple squamous cell carcinomas arising in the oral cavity. Issue 1 (30th April 2013) - Montebugnoli, Lucio; Leonardi, Elisa; Morandi, Luca; Farnedi, Anna; Gissi, Davide Bartolomeo; Marchetti, Claudio; Tarsitano, Achille; Balbi, Tiziana; Gentile, Luciano; Cocchi, Roberto; Foschini, Maria Pia
<x xml:space="preserve">Abstract</x> Background Histological and clinical criteria are generally used to differentiate second primary tumors (SPTs) from local recurrences. The purpose of the present study was to apply mitochondrial DNA (mtDNA) D‐loop analysis to differentiate SPTs from local recurrences and to validate the clinical classification. Methods The study population consisted of 20 consecutive patients presenting multiple oral neoplastic lesions for a total of 25 paired lesions. The mtDNA D‐loop analysis was performed by direct sequencing and phylogenetic clusterization. Results Agreement between mtDNA analysis and clinical classification was found in 19 cases. Discrepancies arose in 6 cases in which the clinical criteria based only on the spatial or temporal distance of the second lesion from the index tumor had led to a diagnosis of SPT (2 cases) or local recurrence (4 cases). Conclusion The present data highlight the value of mtDNA analysis in establishing the clonal relationship between the index tumor and the second neoplastic lesion. © 2013 Wiley Periodicals, Inc. Head Neck36: 94–100, 2014